'Slepen al the nyght with open ye': Personal reflections after 35 years of being on-call. Issue 3 (17th April 2020) - Fitzpatrick, Chris
Abstract : The European Working Time Directive (2003) has had a significant impact in reducing the total number of hours worked per week, as well as shift-lengths. There is, however, no agreement on optimal shift-lengths and day/night work balance in different medical specialities. Given the time it takes for clinical events to unfold, particularly in relation to labour, there may be advantages in retaining the 24 hours on-call shift for obstetricians––in the interests of patient care and training. Increasingly seen as a relic of the past, this shift-length merits further research, which should include the impact on clinician well-being.